Hubungan Profil Pasien Gagal Jantung terhadap Efektivitas Terapi Kombinasi Antihipertensi di Rawat Inap RSUD dr. Loekmono Hadi Kudus - Zulia Tri Rahayu; Eko Retnowati; Galih Kurniawan (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
As one of the cardiovascular diseases, heart failure is a condition in which the heart loses its ability to pump blood adequately to deliver oxygen throughout the body's tissues. According to a WHO survey in 2016, non-communicable diseases such as cardiovascular problems accounted for 38 million out of 56 million total global deaths. Of these, 17.5 million deaths were specifically caused by circulatory system disorders. In Indonesia, heart failure ranks as a leading cause of mortality. Based on the 2018 Basic Health Research (Riskesdas) data, the prevalence rate of heart disease in the country reached 1.5%. Hypertension has been identified as one of the main risk factors that can trigger heart failure. This study aims to analyze the correlation between the profiles of heart failure patients and the effectiveness of combination antihypertensive therapies involving Beta Blocker–ACEI, Beta Blocker–ARB, and Beta Blocker–Diuretic in patients hospitalized at Dr. Loekmono Hadi Regional Hospital, Kudus. The study employed an observational analytic method with a cross-sectional approach using patient medical records. The data were collected from Dr. Loekmono Hadi Regional Hospital, Kudus. The sample population included heart failure patients who received combination antihypertensive therapy (Beta Blocker–ACEI, Beta Blocker–ARB, or Beta Blocker–Diuretic) during their inpatient care in 2024. The sampling technique used was total sampling, with 77 patients meeting the established inclusion and exclusion criteria. Data analysis was performed using univariate and bivariate methods supported by the Chi-Square test. The most commonly used combination therapy was Beta Blocker + Diuretic, administered to 36 patients (46.8%). The average blood pressure of heart failure patients before therapy was 143.81/83.05 mmHg, and after therapy, it was 126.10/76.23 mmHg. Most patients (69 patients or 89.6%) achieved normal blood pressure levels (<140/90 mmHg) post-therapy. Chi-Square analysis indicated a significant correlation between age (p=0.04) and therapy effectiveness. In contrast, no significant association was found between gender (p=1.000) or the type of combination therapy used (p=0.895) and therapeutic outcomes.